Effect of Cassava based diet on lipids concentration in albino rats fed with crude oil contaminated diet - AS Braide; OA Adegoke; EO Bamigbowu (Journal of Applied Sciences and Environmental Management)
The study was carried out to ascertain the effect of a cassava based diet (gari) on lipid profile in albino rats fed crude oil contaminated diets by feeding diet contaminated with various concentrations of crude oil mixed with 20% gari to albino rats to determine the protective effect of gari. The lipid profile (Cholesterol, triglycerides, HDL cholesterol and LDL cholesterol) were monitored in the animals. Gari feeding at 20% caused dose dependent reduction in Cholesterol and LDL cholesterol with dose dependent increases in Triglycerides and HDL cholesterol in gari fed albino rats compared with Petroleum fed albino rats (P<0.05) suggesting that gari reversed the effect of crude oil on changes in lipid profile. Dose dependent increase in cholesterol, LDL cholesterol and dose dependent decrease triglycerides and HDL cholesterol was observed in petroleum fed rats compared with their controls (P<0.05). The study showed that ingestion of petroleum contaminated diet caused increase cholesterol and LDL cholesterol and decreased triglycerides and HDL cholesterol, but supplementation of the diet with 20%Gari lowered the increased concentrations of cholesterol and LDL cholesterol observed in the Petroleum contaminated diet while increasing the triglycerides and HDL cholesterol concentrations. This study showed that feeding on gari diet caused reversed to changes in lipid concentration caused by crude petroleum.